Social Character: Erich Fromm and the Ideological Glue of Neoliberalism. Issue 1 (2nd January 2017) - Foster, Roger
ABSTRACT: Several thinkers have expressed the view that the central nostrums of neoliberalism, including self-reliance, personal responsibility and individual risk, have become part of the "common sense" fabric of everyday life. My paper argues that Erich Fromm's idea of social character offers a comprehensive and persuasive answer to this question. While some have sought the answer to this conundrum in Foucault's notion of governmentality, I argue that, by itself, this answer is not sufficient. What is significant about the notion of social character, I claim, is that it manages to unify "top-down" approaches like governmentality focused on ideas and policy, with "bottom-up" approaches focused on how the insights of day to day experience are mediated through culture. Adapting this theory to neoliberalism, I argue, means that the "common sense" nature of neoliberalism, and the lack of a reckoning for its massive economic failure (as evidenced by the 2007 Great Recession), are explicable through the formation of a neoliberal social character, by means of which experiential processes align with cultural meanings and, subsequently, fuse with social expectations.